Juridical Review Invitation of General Meeting of Shareholders (GMS) at PT. Main Partner Grace (Analysis of Central Jakarta District Court Decision Number 108/Pdt.P/2014/PN.JKT.PST.) - Rahmat Lubis; Bastari; Utary Maharany Barus; Maria; Jefri Ardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study uses normative legal research using statutory approaches (Statute Approach) and case approaches (Case Approach) and data collection in this study uses library research (Library Research). In this study there are 3 (three) main points of discussion. First, the summons for the General Meeting of Shareholders (GMS) by the shareholders at PT. Mitra Utama Award is in accordance with the provisions of the Limited Liability Company Law. Second, regarding the consideration of the panel of judges, it has fulfilled the principles of legal certainty and justice. Third, the legal consequences of the Board of Directors not holding a General Meeting of Shareholders and violating the fiduciary duty principle where if a loss occurs due to negligence by the Board of Directors, the Board of Directors is fully responsible personally and jointly. For this reason, it is hoped that the settlement of this case is through deliberation efforts and following the regulations in the implementing regulations of Law Number 40 of 2007 concerning Limited Liability Companies.